Chiral perovskite optoelectronics - Long, Guankui (2021)
Hybrid organic–inorganic perovskites (HOIPs) offer long carrier diffusion lengths, high absorption coefficients, tunable bandgaps and long spin lifetimes. The flexible crystal structure and ionic nature of HOIPs makes it possible to allow tune their material properties through rational design, including the incorporation of chiral organic ligands. Recently, chiral HOIPs have emerged as promising materials for chiroptoelectronics, spintronics and ferroelectricity. They exhibit high photoluminescence polarization (17% without an external magnetic field), good device performance (a circularly polarized photodetector had 100 times higher responsivity than one based on chiral metasurface) and high saturated polarization (~2 times higher than that of barium titanate). Here we review the latest advances in chiral HOIPs and investigate the specific benefits of combining chiral organic and inorganic components in perovskites. We discuss demonstrations of chiroptical and ferroelectric applications, and conclude with our perspective on the future opportunities for chiral HOIPs.